Connecting hydrology cycle with the strategies of stormwater management for sustainable environmental planning and design - Zen, Ismawi; Tukiman, Izawati; Musa, Mohd Faiz (WorldConferences.net, 2015)
The central idea of strategies of stormwater management is about the environmental sustainability. The environmental sustainability can be achieved by synthesizing the strategies with the hydrology cycle. The reason is strategies of stormwater management are about the process to replicate the hydrology cycle. The connection between the strategies and hydrology cycle are crucial to be analysed and highlighted to help designer in understanding and making accurate planning and design of the strategies to reduce the quantity and to improve the quality of stormwater. Thus, the aim of this study is to analyse the strategies of sustainable stormwater management with the hydrology cycle. Two objectives were formulated: (i) to identify the strategies of sustainable stormwater management, and (ii) to analyse the connection of the identified strategies with hydrology cycle. In this qualitative approach study, three methods were applied for data collection - online journal, forum discussion and e-mail interview. The collected data was analysed based on five steps of descriptive comparative analysis. Subsequently, 17 strategies have been identified and listed according to the priority connection with 7 hydrology cycles - interception, infiltration, surface runoff, depression storage, evapotranspiration, groundwater flow and interflow. The strategies were synthesized with hydrology cycle as an analysis factor of environmental sustainability to list the strategies in priority order. The list of the strategies are infiltration basin, barrier system, greenways, stream reclamation, vegetated surface channel, rainwater harvesting, narrow street, rain garden, stormwater wetland, tree canopy cover, green roof, disconnection of impervious area, porous pavement and soil modification.